Leishmania eukaryotic elongation Factor-1 beta protein is immunogenic and induces parasitological protection in mice against Leishmania infantum infection. (February 2021) - Santos, Thaís T.O.; Machado, Amanda S.; Ramos, Fernanda F.; Oliveira-da-Silva, João A.; Lage, Daniela P.; Tavares, Grasiele S.V.; Mendonça, Débora V.C.; Cardoso, Mariana S.; Siqueira, Williane F.; Martins, Vívian T.; Ludolf, Fernanda; Reis, Thiago A.R.; et al.
Abstract: Treatment for visceral leishmaniasis (VL) is hampered mainly by the toxicity and/or high cost of antileishmanial drugs. What is more, variability on sensitivity and/or specificity of diagnostic tests hinders effective disease management. In this context, prophylactic vaccination should be considered as a strategy to prevent disease. In the present study, immunogenicity of the Leishmania eukaryotic Elongation Factor-1 beta (EF1b) protein, classified as a Leishmania virulence factor, was evaluated in vitro and in vivo and tested, for the first time, as a vaccine candidate against Leishmania infantum infection. The antigen was administered as DNA vaccine or as recombinant protein (rEF1b) delivered in saponin. BALB/c mice immunization with a DNA plasmid and recombinant protein plus saponin induced development of specific Th1-type immunity, characterized by high levels of IFN-γ, IL-12, GM-CSF, both T cell subtypes and antileishmanial IgG2a isotype antibodies, before and after infection. This immunological response to the vaccines was corroborated further by parasitological analysis of the vaccinated and then challenged mice, which showed significant reductions in the parasite load in their liver, spleen, bone marrow and draining lymph nodes, when compared to the controls. Vaccination using rEF1b/saponin induced a more robust Th1 response and parasitological protection when compared to the DNA vaccine. Furthermore, in vitro analysis of lymphoproliferation, IFN-γ and IL-10 levels in human PBMC cultures showed as well development of a specific Th1-type response. In conclusion, data suggest that EF1b could be a promising vaccine candidate to protect against L. infantum infection. Graphical abstract: Image 1 Highlights: The eukaryotic elongation factor-1 beta protein was tested against L. infantum. The antigen was administered as DNA vaccine or recombinant protein plus adjuvant. Vaccinated mice mounted a Th1-type immune response before and after infection. Lower parasite burden was found in distinct organs using both vaccination schedules. The recombinant protein plus adjuvant induced better response than DNA vaccine.